Faktor-faktor yang Mempengaruhi Kepuasan dan Loyalitas Pelanggan di Restoran selama Pandemik Covid-19 - Kezia Stevany; Axel Gian Aditama; Agrita Alba Rosalina; Felicia Tri Sulistyo; Valerian Andre; Istijanto Istijanto (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
Research on customer loyalty in the fast food restaurants in JABODETABEK is still scarce despite the increase in fast food consumption in Indonesia. Moreover, there has been no research on fast food restaurants during COVID-19 pandemic in JABODETABEK. The purpose of the study is to analyze the effect of food quality, price, location and environment, service quality, social enjoyment, cleanliness on customer satisfaction and the effect of customer satisfaction on consumer loyalty in the fast food restaurants in JABODETABEK during COVID-19 pandemic. Data collection techniques using Google Forms. There were 341 respondents chosen by purposive sampling technique as samples of this study. Methods of data analysis using SPSS version 26. This study found that food quality, price, service quality, social enjoyment, and cleanliness had a positive effect on customer satisfaction with cleanliness being the most influencing factor of customer satisfaction. On the other hand, location and environment had insignificant effect on customer satisfaction. Meanwhile, customer satisfaction has a positive effect on customer loyalty in the fast food restaurants in JABODETABEK.